APPLICATION OF REMOTE SENSING IN LITHOLOGICAL DISCRIMINATION OF PRECAMBRIAN BASEMENT ROCKS OF ZUNGERU AREA, PART OF SHEET 163 (ZUNGERU NW), NORTH CENTRAL NIGERIA (FUDMA JOURNAL OF SCIENCES, 2021)
Remote sensing technology has advanced significantly, making it useful for geological applications such as structural and lithological mapping, as well as mineral prospecting and mapping. This study looks at how certain enhancement techniques on Landsat 7 ETM+ data can be used to map surface geology, resulting in color composite imagery that can be interpreted and validated through field mapping exercises. Because some of these rocks are poorly exposed and some portions of the research region are inaccessible, field mapping was supplemented by remote sensing lithological mapping techniques. False Color Composite images for bands (7:4:1 and7:5:4), Principal Component analysis (PC1, 2, 3 and PC4, 5, 6) and RGB composite images of Landsat band ratios (1/3:5/7:3/5 and5/1:5/7:4) proved useful in determining the approximate boundaries of the various lithology in the research area. Gneiss and quartzites occur in the central and western quadrants of the study area, mylonites and schist in the eastern quadrant, and amphibolite in the southern and southeastern quadrants, according to GPS sample locations of the individual rock types found in the study area plotted on the processed images. The contact relationships between these rocks are mostly gradational and interlayered. As a result, a thorough examination of satellite optical imagery, such as Landsat data, can greatly aid lithological inquiry and the creation of more detailed geological maps in areas that are inadequately understood.
Keywords: Band Ratio, False Colour Composite images, Landsat 7 ETM , Principal Component Analysis